Global and Critical Visions of Distance Universities and Programs in Latin America - Casas Armengol, Miguel (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2002)
The future of any region’s higher education infrastructure cannot be a matter of guesswork; instead it must be built upon a solid foundation that is both rationally and soundly constructed. This postulate is especially important for regions such as Latin America experiencing problems associated with underdevelopment. Universities, particularly those specializing the area of science and technology, can and do play a constructive role in the advancement and improvement of modern society. However, the current Latin American educational context, which is less than optimal, can be compared with other similarly developing countries around the world, many of which have produced high quality university and scientific systems. Why is Latin America lagging behind? This is a good question that deserves closer examination. This article discusses reasons for the chronic problems for the deteriorated conditions facing Latin American universities. It also suggests ways in which Latin American distance universities can contribute to a transformation of the entire university system throughout the region.